Improving Volleyball Learning Results Through The Web at Junior High Scool Country 1 Tanjung Batu - Destriani, Destriani; Alfarandi, Reza; Bayu, Wahyu Indra (Journal of Physical Education Health and Sport, 2023)
This research aims to determine the improvement in learning outcomes through the D, Volleyball Learning web in volleyball learning at SMA Negeri 1 Tanjung Batu. This research uses classroom action research (PTK) using two action cycles. The research instruments are cognitive (knowledge), psychomotor (skills) bottom serve, smash, affective (attitude) tests. This data collection technique uses bottom service tests, smash, observation and documentation. The test data analysis technique uses learning completeness. The subjects used in this research were 31 students in class VIII.2, 11 male students and 20 female students. Based on the results and discussion of the research, it was found that in the first cycle of assessing students' knowledge, the percentage of completeness reached 32.2% with an average score of 58.6. Assessing students' lower service skills, the percentage of completion reached 32.2% with an average of 45.4. Assessing students' smash skills, the percentage of completion reached 41.9% with an average of 64.4. The assessment of students' attitudes, the percentage of completeness reached 61.2% with an average of 70.9. Then in cycle II, the results of assessing students' knowledge, the percentage of completeness reached 83.8% with an average score of 79.3. The assessment of lower service skills, the percentage of completion reached 83.8% with an average score of 75. The assessment of students' smash skills, the percentage of completion reached 87.1% with an average of 74.7. Assessment of students' attitudes, the percentage of completeness reached 80.7% with an average of 77. From the results of observations, students' activeness increased, in cycle I the percentage of students' activeness reached 65.1% in the active category and in cycle II it increased by percentage 80% are very active, so it can be concluded that the implementation of the D, Volleyball Learning web media is effectively used in learning volleyball at SMP Negeri 1 Tanjung Batu.